Pandemic, Participatory Culture and Reinvention of Everyday Life - Saba Ayon, Hadi (Jurnal InterAct, 2021)
How do we define participation during a pandemic? Are we in an era that requires reinventing our physical space and our modes of participation to build a new society? The novel coronavirus has deconstructed social space as we know it, and significantly disrupted our participation in its spheres. Today we are witnessing new forms of space, in the light of the ongoing pandemic and its impact on our participation, physical space and digital culture. This article demonstrates changes that occur in the physical and connected spaces that form our “new virtual urbanism” (Doueihi, 2011). It describes participation practices in natural parks in a Geneva-Switzerland and the Pays de Gex-France, distinguishing three types of spaces: the pre-pandemic space, the confinement space and the deconfinement space. It shows how socio-cultural practices changed in relation to the configuration of the space and the use of digital technology. Will we need to reinvent our space to encourage participation? The answer lies perhaps in considering the development of our digital traces and harvesting them in organized projects with rules, purpose, administration, management and governance. In this sense, digital participation becomes full and efficient when it relies on the process of building a memory and includes those who find themselves excluded from this new world.